Identification of native fruit species with productive potential in danger of extinction in the province of Huaura - Díaz Pillasca, Hermila Belda (2020)
The present research work aimed to identify the native fruit species with productive potential in danger of extinction in the province of Huaura, as well as evaluate the functional properties of the identified species and estimate their performance, production and productivity. In order to identify the functional species in danger of extinction in the province of Huaura, in addition to the technique of pragmatic attitude and observation, interview techniques were applied to farmers, in order to determine species with minimal or no population density. and productivity. The native fruit species classified as endangered in the province of Huaura are Campomanesia lineatifolia "palillo" and Bunchosia armeniaca "cansaboca", because they are cultivated by a small number of farmers, not for commercial purposes but as decoration and harvesting its fruits at the family level; reason for which a minimum or no agronomic management is dedicated to them. Campomanesia lineatifolia “palillo” and Bunchosia armeniaca “cansaboca” are identified as the functional species of native fruit trees threatened with extinction in the province of Huaura, placing them in the category of “critically endangered”, in addition to presenting functional properties and with high rates of economic and biological productivity.